Effects of "Environmental Chatter" about Age and Aging on Middle-Aged and Older Adults' Communication and Perceptions of Aging Efficacy. Issue 1 (1st January 2020) - Gasiorek, Jessica; Fowler, Craig
Abstract : Grounded in the communicative ecology model of successful aging (CEMSA), this study examined how social messages individuals encounter about age predicted efficacy regarding aging. Data from N = 283 middle-aged and older American adults were analyzed via path analyses. Explicit messages about aging, the presence of positive and negative role models for aging, and the degree to which intergenerational interaction was experienced as accommodative and nonaccommodative predicted how participants themselves communicated about aging. Having positive role models and quality of intergenerational interaction also predicted self-reports of efficacy related to aging.